Efektivitas Pendekatan TPACK dalam Pembelajaran PAI untuk Meningkatkan Literasi Digital Siswa di SMAN 9 Padang - Robi Aroka (Jurnal Pendidikan Tuntas, 2024)
This study aims to enhance students' digital literacy in Islamic Religious Education (PAI) through the Technological Pedagogical Content Knowledge (TPACK) approach. The research was conducted in grade XI at SMAN 9 Padang over two cycles, each consisting of planning, implementation, observation, and reflection stages. The results revealed that the TPACK approach significantly improved students' digital literacy. In the first cycle, the students' digital literacy mastery reached 56%, increasing to 85% in the second cycle. This approach integrated technology, pedagogy, and content to create an interactive and relevant learning experience. The success was supported by the use of digital media, such as interactive videos and presentation applications, as well as student collaboration in group discussions. The study concludes that the TPACK approach effectively enhances students' digital literacy while improving their understanding of PAI materials.